Effects of Zn-EDTA on the health and welfare of the African catfish, Clarias gariepinus (Burchell, 1822), in a recirculating aquaculture system - Hildebrand, Marc-Christopher; Rebl, Alexander; Goldammer, Tom; Palm, Harry Wilhelm; Baßmann, Björn (Frontiers in Aquaculture, 2024)
As nutrient-rich water in aquaponic systems cannot supply growing plants with all the required trace elements, supplementation with specific fertilizers is performed to make up for this deficit. While chelated fertilizers such as ethylenediaminetetraacetic acid–zinc disodium complex (Zn-EDTA) are becoming more popular in this context for improving plant growth in aquaponic systems, little is known about their effects on fish. During two experiments, a total of 576 individuals of catfish fry (0.19 g) and fingerlings (220.01 g) of the African catfish (Clarias gariepinus; Burchell, 1822) were kept separately for 32 days under experimental aquarium conditions. The fry was exposed to 0.125 and 0.5 mg/L, while the fingerlings were exposed to 0.5 and 2.0 mg/L Zn-EDTA in a plantless aquaponic system. The third treatment group consisted of a control group without Zn-EDTA. The growth, mortality, and ethological indicators were assessed for all growth stages, while the leukocyte distribution and histopathological changes were additionally determined for the fingerlings. As the feed intake in the experiment was limited, the investigations were focused on the effects of Zn-EDTA and not on the growth process of a respective fish growth stage. While the growth, mortality, and behavior were not significantly different in both growing stages, the number of mature neutrophils changed significantly in all treatments in fingerlings. Zn was not detected in the histologically investigated organs at the tested concentrations using the staining method. However, morphological alterations of the gill epithelium were found on the secondary lamellae. Quantitative multiplex PCR was used to simultaneously evaluate the expression of 17 genes related to Zn metabolism and stress physiology in head kidney samples. The transcripts of several selected genes changed by up to 70-fold. Due to high individual variances, only the copy numbers of the KMT2A (lysine-specific methyltransferase 2a) gene were significantly different across treatment groups and sampling points. However, the present results indicate that the addition of Zn-EDTA at the tested concentrations can be considered relatively benign for the health and welfare of C. gariepinus, as no toxic effects of Zn-EDTA were observed in moderately hard to hard water.